Carbon monoxide exposure assessment among toll operators in Klang Valley, Kuala Lumpur, Malaysia - Samsuddin, Niza; Hashim, Jamal Hisham (Taylor and Francis Ltd, 2007)
A comparative cross-sectional study was conducted to determine tollbooth carbon monoxide (CO) levels and carboxyhaemoglobin (COHb) levels among the tollbooth operators and office workers in the Klang Valley, Kuala Lumpur. All tollbooths were equipped with well functioning air-conditioning. The total number of respondents was 180: 90 toll operators and 90 office workers aged between 19 and 52 years. The highest peak of CO level recorded was 61 ppm. The highest average peak CO level within a shift was 30 ppm. The CO level was higher during peak traffic at 6.00 – 8.00 a.m. There was no significant correlation between average peak CO level with vehicle load (r = −0.007, p = 0.474). The toll operators' median COHb level (1.0%, IQR = 0.8%) was significantly higher (p = 0.008) compared to office workers (0.7%, IQR = 0.8). There was a weak and significant correlation between COHb levels with average peak CO levels (r = 0.228, p = 0.031). In conclusion, tollbooth operators were chronically exposed to CO leading to higher COHb levels compared to office workers.